Cultural Diversity and Paleomobility in the Andean Middle Horizon: Radiogenic Strontium Isotope Analyses in the San Pedro De Atacama Oases of Northern Chile. Issue 2 (June 2014) - Knudson, Kelly J.; Torres-Rouff, Christina
Abstract : Despite a long history of research, interactions between the Tiwanaku polity of the Andean Middle Horizon (ca.A.D. 500-1100) and the San Pedro de Atacama oases of northern Chile remain controversial. Here, we investigate Middle Horizon interactions through an isotopic identification of the geographic origins of individuals buried in San Pedro de Atacama cemeteries and present the largest radiogenic strontium isotope dataset generated, to date, for the Andes. For individuals in Middle Horizon San Pedro de Atacama cemeteries ofCasa Parroquial, Coyo Oriental, Coyo-3, Larache, Quitor-5, Solcor-3, Solcor Plaza, Solor-3, and Tchecar Túmulo Sur, mean tooth enamel and bone 87 Sr/ 86 Sr = .70834 ± .00172 (2σ, n = 273). Overall, the mean 87 Sr/ 86 Sr values from Middle Horizon San Pedro de Atacama cemeteries support the idea that interactions between Atacameños and inhabitants of other regions varied by ayllu, an Andean kin-based community structure, with some ayllus incorporating individuals with a wider variety of geographic origins than others. When our interpretations of the radiogenic strontium isotope data are contextualized with analyses of mortuary behavior and recent biodistance analyses, we argue that the San Pedro de Atacama oases appear to be have been inhabited by culturally and biologically diverse groups, rather than by large numbers of colonists from the Tiwanaku capital and the Lake Titicaca Basin.